Quizizz in EFL Classroom Learning: Students’ Perception and Challenges - Kartika, Ni Luh Putu Indah; Budiarta, Luh Gd Rahayu (STKIP AGAMA HINDU SINGARAJA, 2025)
This study investigates the perceptions of students regarding the implementation of Quizizz in a public school in Bali, as well as the challenges they face. Despite the growing popularity of digital tools in education, there is limited research specifically focusing on the perceptions and challenges of EFL students in Indonesia regarding the use of Quizizz. Employing a mixed-method explanatory sequential design, the research involved 34 English as a Foreign Language (EFL) students. Data collection included a questionnaire, designed based on the U.T.A.U.T. theory using a Likert scale, and an interview guide developed from Savinna’s theory, consisting of six questions. The findings reveal that students generally hold a positive perception of Quizizz in EFL classes, noting that it enhances their motivation and participation. However, they also encounter several challenges, including unstable internet connections, inadequate device performance, and difficulties with certain Quizizz features that complicate their experience when faced with challenging questions.